DEVELOPMENT OF SOCIAL INSURANCE SYSTEM OF WORKERS AND EMPLOYEES IN AUSTRIA IN 50-80-ies IN THE 19th CENTURY - Irina V. Lokhova (Вестник Северо-Кавказского федерального университета, 2022)
The candidate represents the Department of Ancient History and the Middle Ages (North Ossetian State University named after K.L. Khetagurov). Summary: the present article shows the specific features of the social legislation development in Austria in 50-80-ies in the 19th century.The author comes to the conclusion that besides internal factors German experience influenced on social policy in Vienna.